La poesia di Giovanni Pietro Arrivabene - Bologna, Orazio Antonio (Collectanea Philologica, 2016)
With this brief study, first the author deals with the poetry by Giovanni Pietro Arrivabene. In fact, for the first time he has published a long Latin poem of the poet preserved in a single manuscript in Pienza, in the library, which was of Pio II. The poet, who lived during the Renaissance, had a very careful preparation at the school of Francesco Filelfo, the most appreciated humanist after Enea Silvio Piccolomini. With the Carmen in Pii Pontificis laudem… Arrivabene hoped to enter in the courtyard of the Pope; but Pius II, even though he appreciated the poem, written on fine parchment, didn’t take the young poet into account, who was only twenty years. The scholar, on the one hand, thought back to the formation and the aspirations of the young poet, on the other the cultural character of his age, in which Giovanni Pietro Arrivabene spent his life. Short, but useful hints are devoted to the wonderful court of Mantua, where the poet spent twenty years at the service of the cardinal Francesco Gonzaga.